A REVIEW ON THE LATEST TRENDS IN INTERNATIONAL HIGHER EDUCATION - Maybelle A. Paulino (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Globalization and regionalization have caused worldwide students’ mobility to accelerate at an unprecedented rate. The said increasing students’ movement upshots to the growth in the number of international students globally. As a consequence, most host countries and their respective higher education institutions (HEIs) are vying for international students’ recruitment and enrolment. While most host countries are working towards maintaining their statuses as the current hub for international education, well-liked host of branch campuses, and popular study destination, the Philippines, despite the initiatives and sound marketing strategies of most of its HEIs, cannot attract and recruit a good number of international students. This article aims to explore the latest trends in international higher education. To better understand the current international higher education landscape and to contribute to solving the problem mentioned above, the study reviews the extant literature for recent developments in the field of international higher education. This assessment of international higher education industry is significant for proper strategies fitting. The examinations revealed that the present international higher education has been experiencing significant transformations that critically affect the behaviors of many host countries and HEIs, globally. The study explicates the findings and deliberately offers some essential implications to host countries, higher education institutions, and future researches.